Tuberculosis in swine co-infected with Mycobacterium avium subsp. hominissuis and Mycobacterium bovis in a cluster from Argentina - Barandiaran, Soledad (2015)
In Argentina little is known about the epidemiology of tuberculosis (TB) infection in swine. We characterized the epidemiological dynamics of Mycobacterium avium complex (MAC) infection in a swine population of Argentina using molecular tools and spatial analysis techniques. Isolates (n = 196) obtained from TB-like lesions (n = 200) were characterized by polymerase chain reaction. The isolates were positive to either M. bovis (IS6110) (n = 160) or M. avium (IS1245) (n = 16) while the remaining 20 (10·2%) isolates were positive to both M. bovis and M. avium. The detection of both bacteria together suggests co-infection at the animal level. In addition, MAC-positive isolates (n = 36) were classified as M. avium subsp. avium (MAA) (n = 30) and M. avium subsp. hominissuis (MAH) (n = 6), which resulted in five genotypes when they were typed using mycobacterial interspersed repetitive unit, variable number of tandem repeats (MIRU-VNTR). One significant (P = 0·017) spatial clustering of genotypes was detected, in which the proportion of MAH isolates was larger than expected under the null hypothesis of even distribution of genotypes. These results show that in Argentina the proportion of TB cases in pigs caused by M. avium is larger than that reported in earlier studies. The proportion of M. bovis–MAC co-infections was also higher than in previous reports. These results provide valuable information on the epidemiology of MAC infection in swine in Argentina.